2008
DOI: 10.1083/jcb.200708123
|View full text |Cite
|
Sign up to set email alerts
|

WASP family members and formin proteins coordinate regulation of cell protrusions in carcinoma cells

Abstract: We examined the role of the actin nucleation promoters neural Wiskott-Aldrich syndrome protein (N-WASP) and WAVE2 in cell protrusion in response to epidermal growth factor (EGF), a key regulator in carcinoma cell invasion. We found that WAVE2 knockdown (KD) suppresses lamellipod formation and increases filopod formation, whereas N-WASP KD has no effect. However, simultaneous KD of both proteins results in the formation of large jagged protrusions with lamellar properties and increased filopod formation. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 53 publications
11
119
0
Order By: Relevance
“…Furthermore, if the convergent elongation model was physiologically relevant, one would expect an interference with the process by removal of lamellipodia, as previously proposed (Biyasheva et al, 2004). Although a more recent study has reaffirmed this conclusion in neurons (Korobova and Svitkina, 2008), several independent studies have continuously failed to establish a defect in filopodia initiation and protrusion effected by suppression of lamellipodia (Gomez et al, 2007, Nicholson-Dykstra and Higgs, 2008, Nobes and Hall, 1995, Sarmiento et al, 2008, Vidali et al, 2006. These and similar conflicting observations have prompted researchers to propose different "types" of filopodia, or distinct, cell-type-dependent mechanisms of filopodium formation (see e.g.…”
Section: Models For Filament Generation In Filopodia: Convergent Elonmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, if the convergent elongation model was physiologically relevant, one would expect an interference with the process by removal of lamellipodia, as previously proposed (Biyasheva et al, 2004). Although a more recent study has reaffirmed this conclusion in neurons (Korobova and Svitkina, 2008), several independent studies have continuously failed to establish a defect in filopodia initiation and protrusion effected by suppression of lamellipodia (Gomez et al, 2007, Nicholson-Dykstra and Higgs, 2008, Nobes and Hall, 1995, Sarmiento et al, 2008, Vidali et al, 2006. These and similar conflicting observations have prompted researchers to propose different "types" of filopodia, or distinct, cell-type-dependent mechanisms of filopodium formation (see e.g.…”
Section: Models For Filament Generation In Filopodia: Convergent Elonmentioning
confidence: 84%
“…However, more recent observations indicated that this assumption was preliminary . For instance, neither N-WASP, a direct Cdc42-effector and activator of the actin nucleating machine Arp2/3-complex (Stradal et al, 2004) nor Arp2/3-complex itself turned out to be essential for filopodia formation (Gomez et al, 2007, Lommel et al, 2001, Nicholson-Dykstra and Higgs, 2008, Sarmiento et al, 2008. However, conflicting studies reported filopodia reduction (but not removal) upon Arp2/3-complex silencing (Korobova and Svitkina, 2008) or N-WASP deletion (Snapper et al, 2001).…”
Section: Rho-gtpasesmentioning
confidence: 91%
“…In neuronal cells, RhoA activity is necessary for the formation of filopodial protrusion induced by RhoA/ROCK signaling (Chen et al, 2006;Kim et al, 2010). Furthermore, activation of mammalian diaphanous-related formin (mDia), which is known as an effector of RhoA, localizes at the filopodia, promotes actin filament assembly and contributes to filopodia formation (Faix and Grosse, 2006;Carramusa et al, 2007;Sarmiento et al, 2008). Therefore, ARAP3 may suppress the cell adhesion, migration and invasion of cancer cells by inhibiting RhoA signaling through its Rho-GAP domain.…”
Section: Discussionmentioning
confidence: 99%
“…45 For example, RhoA is required for mDIA1-induced filopodia at the front of N-WASP/WAVEdepleted carcinoma cells. 37 Whilst it is not possible to look at the formation of filopodia during TEM in RhoA-depleted T cells as these cells do not initiate TEM, it would be interesting to examine whether proteins involved in filopodium formation in other cell types, such as vasodilator-stimulated phospho-protein (VASP), fascin, insulin receptor substrate p53 (IRSp53) and myosin X, 47 localize to the structures we observe in transmigrating T cells. The mDIA proteins are likely…”
Section: A Possible Role Of Rhoa In Filopodia During T Cell Temmentioning
confidence: 99%
“…33,34 Interestingly WiskottAldrich syndrome protein (WASP) 35 and mDIA1 co-operate at the leading edge during neutrophil migration. 36 The balance of activity between N-WASP, WASP family Verprolin homologous (WAVE) proteins and formins has also been shown to regulate the type of actin filament structures that are formed at the leading edge of carcinoma cells, 37 suggesting a complex interplay between these different actin regulators. It is thus possible that RhoA and Rac2 activate different actin regulators at the front of T cells that act together to induce lamellipodial protrusion.…”
Section: Rhoa Is Required For Lamellipodium and Uropod Formation In Tmentioning
confidence: 99%